Insights into myosin regulatory and essential light chains: a focus on their roles in cardiac and skeletal muscle function, development and disease - Sitbon, Yoel H (J Muscle Res Cell Motil, 2019)
The activity of cardiac and skeletal muscles depends upon the ATP-coupled actin-myosin interactions to execute the power stroke and muscle contraction. The goal of this review article is to provide insight into the function of myosin II, the molecular motor of the heart and skeletal muscles, with a special focus on the role of myosin II light chain (MLC) components. Specifically, we focus on the involvement of myosin regulatory (RLC) and essential (ELC) light chains in striated muscle development, isoform appearance and their function in normal and diseased muscle. We review the consequences of isoform switching and knockout of specific MLC isoforms on cardiac and skeletal muscle function in various animal models. Finally, we discuss how dysregulation of specific RLC/ELC isoforms can lead to cardiac and skeletal muscle diseases and summarize the effects of most studied mutations leading to cardiac or skeletal myopathies.